2005
DOI: 10.1002/adma.200400474
|View full text |Cite
|
Sign up to set email alerts
|

Orientation‐Controlled Growth of Single‐Crystal Silicon‐Nanowire Arrays

Abstract: is higher than that observed for Co 3 O 4 with an average particle size of 20 nm (25 K). [11] This is in accordance with the smaller average particle size, which corresponds to a higher fraction of surface spins, and hence for which bulk behavior is expected to occur at higher temperatures. Relationships between block temperature and particle size have also been studied for Mn 3 O 4 and c-Fe 2 O 3 , and the peak temperature was also found to increase with decreasing particle size.[12]In conclusion, mesostructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 27 publications
6
77
0
Order By: Relevance
“…21,22 By increasing the temperature of substrates, the Au thin film on the Si(111) wafer starts to randomly crack and then evaporate, migrating from the wafer and forming liquid-phase Au nanodroplets of various sizes. This cracking allows Au to be randomly deposited onto a Si(111) wafer and diffuse over the substrate by the two well-known mechanisms of coalescence and Ostwald ripening.…”
Section: Resultsmentioning
confidence: 99%
“…21,22 By increasing the temperature of substrates, the Au thin film on the Si(111) wafer starts to randomly crack and then evaporate, migrating from the wafer and forming liquid-phase Au nanodroplets of various sizes. This cracking allows Au to be randomly deposited onto a Si(111) wafer and diffuse over the substrate by the two well-known mechanisms of coalescence and Ostwald ripening.…”
Section: Resultsmentioning
confidence: 99%
“…On silicon, in contrast to our results, they did not get any epitaxially grown wires whereas on GaAs, they got growth in 110 direction. They assume to have a certain amount of As/Ga dissolved in Au at the initial state of growth and thus incorporation of these species into the nanowire which could result in Ge et al [12] found that supersaturation could be a reason for the growth of silicon nanowires on silicon (111) once vertically and under certain conditions along the other 111 directions.…”
Section: Thermodynamic Consideration Of Silicon and Germanium Nanowirmentioning
confidence: 99%
“…MAC etching used in conjunction with various film patterning techniques has been demonstrated as a promising method for Si NW fabrication [80]. The orientation-controlled growth of Si NW arrays [106,107] and the controlled growth of Si NWs in predetermined configurations [108] have been illustrated. Ultrathin anodic aluminum oxide (AAO) membranes have been utilized as versatile masks for fabricating 2D extended arrays of various functional nanostructures (microelectronics, optoelectronics, and sensing) [109] because of their unique ability to control the pore size and pore density.…”
Section: The Application Of Masks In Conjunction With Mac Etchingmentioning
confidence: 99%